Assessment Of Economic Feasibility For Grid-connected Renewable Energy System For A Household Application In Terengganu - Roslan, Umar; W. M. W, Muda (2016)
This article extends the conference paper 'Simulation-based method to evaluate PVAvind hybrid renewable energy system in Terengganu'. Instead of off-grid system considered in the conference version, inspired by feed-in-tariff introduced by The Government of Malaysia, this article includes grid-connected hybrid renewable energy system to examine their feasibility to be used as power supply for a household in Terengganu. In addition, this article compares the performance of grid-only system and hybrid grid-renewable energy systems in terms of cost of electricity and emission of pollutant. The payback period is also examined based on the current sellback rate. Sensitivity analysis is done to find the best sellback rate for a hybrid grid/PV/wind system to compete with a hybrid grid/PV system. In addition, the most optimal configuration is also determined by varying the value of solar radiation, wind speed and sellback rate. Generally, it is concluded that the hybrid grid/1"V system is the most practicable choice to be used as power generator to supply electricity for a household in Terengganu. Keywords: cost of energy, economic analysis, feed-in-tariff grid-connected system, HOMER software, optimal configuration, payback period, renewable energy, sensitivity analysis.